Clinical-radiomics nomogram for identifying HER2 status in patients with breast cancer: A multicenter study - Fang, Caiyun; Zhang, Juntao; Li, Jizhen; Shang, Hui; Li, Kejian; Jiao, Tianyu; Yin, Di; Li, Fuyan; Cui, Yi; Zeng, Qingshi (Frontiers in Oncology, 2022)
Purpose: To develop and validate a clinical-radiomics nomogram based on radiomics features and clinical risk factors for identification of human epidermal growth factor receptor 2 (HER2) status in patients with breast cancer (BC). Methods: Two hundred and thirty-five female patients with BC were enrolled from July 2018 to February 2022, and divided into a training group (from center I, 115 patients), internal validation group (from center I, 49 patients) and external validation group (from center II and III, 71 patients). Preoperative MRI of all patients were obtained, and radiomics features were extracted by a free open-source software called 3D slicer. The least absolute shrinkage and selection operator regression model was used to identify the most useful features. The radiomics score (Rad-score) was calculated by using the radiomics signature-based formula. A clinical-radiomics nomogram combining clinical factors and Rad-score was developed through multivariate logistic regression analysis. The performance of nomogram was evaluated using receiver operating characteristic (ROC) curve and decision curve analysis (DCA). Results: A total of 2553 radiomics features were extracted, and 21 radiomics features were selected as the most useful radiomics features. Multivariate logistic regression analysis indicated that the Rad-score, progesterone (PR) and Ki-67 were independent parameters to distinguish HER2 status. The clinical-radiomics nomogram, which comprised Rad-score, PR and Ki-67, showed a favorable classification capability, with AUC of 0.87 [95% confidence internal (CI), 0.80 to 0.93] in the training group, 0.81 (95% CI, 0.69 to 0.94) in the internal validation group and 0.84 (95% CI, 0.75 to 0.93) in the external validation group, respectively. DCA illustrated that the nomogram was useful in clinical practice. Conclusions: The nomogram combined with Rad-score, PR and Ki-67 can identify the HER2 status of BC.